Thermally stable and low resistance Ru ohmic contacts to n-ZnO - Kim, HK; Kim, KK; Park, SJ; Seong, TY; Yoon, YS (JAPAN SOC APPLIED PHYSICS, 2002)
We report on a promising metallisation scheme for high-quality ohmic contacts to n-ZnO:Al (n(d) = 3 x 10(18) cm(-3). The as-deposited contact yields a specific contact resistance of 2.1 x 10(-3) Omega.cm(2). However, annealing of the contact at 700degreesC for 1 min results in a resistance of 3.2 x 10(-5) Omega.cm(2). The prolonged annealing treatment causes negligible degradation of electrical and thermal properties. These results indicate that the Ru film would be a suitable scheme for the fabrication of high-performance ZnO-based optical and high-temperature devices.
Keywords: FABRICATION; EMISSION